Communicate with Mastery - Schramm, JD (Ascent Audio, 2020)
Develop your leadership communication Communicating with Mastery provides listeners with a rich treasure trove of frameworks and tools for leadership communication as developed and taught over the past decade at Stanford's Graduate School of Business. Designed for the business leader on the go, it provides you quick access to helpful approaches to vexing communication problems leaders face today in speaking and writing to various audiences. Projects often fail not because of the vision, but in the articulation of that vision. With the help of this book, you'll learn how to ensure you get the results you desire as a leader and communicator, including: speak with conviction and write with impact; tailor your communication to any goal, setting, or audience; and scale your leadership through effective coaching. Every time you write or speak, you need to make your words count. And this book shows you how.